Is there a global right to democracy? : a philosophical analysis of peacekeeping and nation building - Pubantz, Jerry, 1947- (Edwin Mellen Press, 2012)
This is an expansive study of what we call "The Global Right to Democracy." The idea gestates from a late 20th century reading of Immanuel Kant. This book is the first comprehensive look at the intersection of neo-Kantian theory and democratization programs undertaken by international organizations and non-governmental bodies in post-conflict and fragile states. The features of this new, assumed right, seem to graft onto international law--and thus hand over to international agencies--methods of protecting and effecting 'democracy' in its broadest definition. The consequence seems to be an alt.